Finansial Inklusi dan Akses Kredit untuk UMKM: Sebuah Analisis Bibliometrik - Judijanto, Loso; Novitasari, Salwa Aulia; Sudarmanto, Eko (Westscience Press, 2024)
This study conducts a bibliometric analysis to explore the research landscape of financial inclusion, analyzing thematic clusters, research trends, author collaboration networks, and identifying potential areas for future research. Utilizing VOSviewer for network visualizations, we examine data from key publications spanning several decades to determine how research foci have evolved. Our findings reveal that research on financial inclusion encompasses a diverse range of themes, including core financial services, digital finance, microfinance, and the socioeconomic impacts of financial accessibility. Trends indicate a progressive shift towards integrating digital solutions and sustainability into financial practices. Author collaboration analysis highlights a robust network of scholars, with significant contributions from leading figures in the field. The study also identifies under-researched areas such as gender-specific financial inclusion and sustainable finance, presenting opportunities for future explorations. These insights contribute to understanding the dynamic and multidimensional nature of financial inclusion research, highlighting its role in fostering economic development and addressing global challenges.